A prática docente na residência pedagógica: relatos de experiência - Costa, Ranyell Lima (Universidade Federal do Tocantins, 2023)
Learning is a process associated with personal development, skills, behaviors, abilities, knowledge and values that are acquired or modified through experience, observation, study and reasoning. Geography is concerned with the transformation of space and the transformations that occur in the world context, and the teaching of Geography is fundamental, o it encompasses different dimensions (political, economic, social, environmental and cultural). The geography teacher is able to observe the changes that take place in the school environment, and thus bring innovations to the teaching of geography, so that the teaching of geography is not merely in the traditional way. In this way, pedagogical practices are important in teaching and so this work aims to present experiences in the Pedagogical Residency program that took place at the Cem Florêncio Aires school in Porto Nacional –To, developed by the academics of the Geography degree course at the Federal University of Tocantins, in period 2018 to 2019. The pedagogical residency program aims to promote the immersion of the licentiate in the basic education school and this immersion must include, among other activities, the pedagogical intervention, something that was experienced and presented in this work.